Auditoría de seguridad en la central digital de la Corporación Nacional de Telecomunicaciones Filial Machala aplicando la norma ISO 27001 - Añazco Romero, Verónica Alexandra (2009)
Our thesis consists of an audit of securities in the National Telecommunications Corporation of the city of Machala applying rules to protect files on the Digital Central department of this organization which is considered critical based on the ISO 27001 standard.